Burned Region Analysis using Normalized Burn Ratio Index (NBRI) in 2019 Forest Fires in Indonesia (Case study : Pinggir-Mandau District, Bengkalis, Riau) - Risty Khoirunisa; Mucsi Laszlo (Geographica: Science and Education Journal, 2020)
Forest fire is a hazard that common to happen in Indonesia every year, whether from natural or human-induced factor. These fires can be uncontrollable and destruct the forest. Furthermore, these can affect the health of the people, the biodiversity, the disruption in transportation and the socioeconomic of the affected region. The total area calculated was burned is 875.756 hectares in the entire country in 2019, the biggest lost after 2015. Thus, the study conducted in some affected area in Riau Province, Sumatra, Indonesia where consistently suffered from the fire by remote sensing and GIS approach. The study of the burned area was investigated using a formulated index called NBRI (Normalized Burn Ratio Index) based on Near Infrared (NIR) and Shortwave Infrared (SWIR) spectral reflectance of Landsat 8 OLI/TIRS Satellite Imageries. The two values of NBRI from post and pre-fire images were calculated to define differenced NBR (dNBR) to assess its severity. It is found that about 4,7 %, or about 11.014 hectares of the area of the study which was about 234.864 hectares was burned. 90,3 % of the burned area was located in the vegetated area, especially forest area with 50,25 % of those cover the burned area. The validation was using visual interpretation based on SPOT 7 pansharpened images resulted in acceptable agreement with kappa coefficient value of 0,83. The information on the maps can be used to develop rehabilitation planning or predict the area for potential fire hazard in the future.